The Jesus Movement in the Perspective of Social Science Evaluation Studies: Review of From Christ to Christianity: The Emergence, Development, and Transformation of the Jesus Movement - XIE, Yilin (Journal of Research for Christianity in China (JRCC), 2022)
Wang Xuesheng, From Christ to Christianity: The Emergence, Development, and Transformation of the Jesus Movement. New Taipei: Taiwan Christian Literature Press / Chung Yuan Christian University Center for Christian and Chinese Cultural Studies, 2016 edition. Paperback, with black-and-white illustrations and tables. Includes 18 pages of foreword, table of contents, and edition citation notes. Main text: 448 pages. Price: NT$570.